2012
DOI: 10.1126/scitranslmed.3003967
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of Mutated ALK Induces Neuroblastoma in Transgenic Mice

Abstract: ALK inhibitors induce complete tumor regression in a mouse model of ALK-driven neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 23 publications
(44 reference statements)
9
139
1
Order By: Relevance
“…However, due to abdominally located tumors in the TH-MYCN mice, it is challenging to determine an objective endpoint to monitor the longitudinal effects of the treatment. Facilitated by imaging tools, several well-established murine models of neuroblastoma should be used, in order to further explore the mechanistic insights and longitudinal impact of combination immunotherapy (51)(52)(53)(54). Taken together, we conclude that tumor-driven CSF-1R signaling regulates the induction of suppressive myeloid cells, which hampers antitumor effects of checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to abdominally located tumors in the TH-MYCN mice, it is challenging to determine an objective endpoint to monitor the longitudinal effects of the treatment. Facilitated by imaging tools, several well-established murine models of neuroblastoma should be used, in order to further explore the mechanistic insights and longitudinal impact of combination immunotherapy (51)(52)(53)(54). Taken together, we conclude that tumor-driven CSF-1R signaling regulates the induction of suppressive myeloid cells, which hampers antitumor effects of checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…To validate how well the cell line-based ALK downstream transcriptional profile recapitulates ALK oncogenic activity, we evaluated ALK signature scores in 2 independent gene expression datasets consisting of respectively 252 and 283 neuroblastoma tumors (19,24,25), as well as data of 2 in vivo neuroblastoma model systems (20). In human primary tumors with ALK amplification or ALK mutations, ALK signature scores were significantly higher than ALK wild-type tumors ( Fig.…”
Section: Aldh6a1mentioning
confidence: 99%
“…Next, a stringent cross-species genomics analyses for differentially expressed genes in MYCN-versus ALK F1174L -driven murine neuroblastoma tumors (16,20), yielded 7 genes expressed significantly higher in ALK F1174L ;DBH-iCre-positive neuroblastoma tumors. In addition to 3 known MAPK-regulated genes (SPRY4, DUSP6, ETV5), also 4 neuronal markers were identified: RET, ENC1, VGF, and VIP.…”
Section: Mutant Alk Upregulates Markers Of Adrenergic and Cholinergicmentioning
confidence: 99%
“…Activation of ALK increases the expression of MYCN by enhancing the activity of the MYCN promoter and stabilizing MYCN protein likely via activation of AKT and ERK pathways [9][10][11]. In vivo, compared to ALKF1174L and MYCN alone, co expression of these two oncogenes leads to the development of neuroblastoma tumors with earlier onset, higher penetrance and enhanced lethality [10,12,13]. In our recent study, neuroblastoma cells harboring both ALKF1174L mutation and MYCN amplification showed less responsive to an ALK inhibitor, crizotinib, comparing to other variants [14].…”
Section: Introductionmentioning
confidence: 99%